(untitled) (ModaPalavra e-periódico, 2016)
These premises, this research aimed to propose procedures, using as a reference the design methodology of Löbach for development of sustainable textile products from leftovers from materials of micro and small manufacturing. The methodology used was bibliographical research to which constitutes the basic procedure for the monographic studies and exploratory research because it does not require the formulation of hypotheses to be tested. She is restricted by set goals, get more information about a particular subject to study and identify the best method to be used, in the case of this project, the idea was to adapt the Löbach synthesis in the design process, linking it with the problem-solving processand the creative process, on four key initiatives to clearly define the problem (preparation); gather information about the problem, analyze them and relate them creatively with each other (generation); create alternative solutions to the problem, judgingthe second criteria (evaluation) and develop the most suitable alternative, establishing the (realization). After the elaboration of the project proved that the methodology used proved to be viable for the development of sustainable products, geared to society and consumption.